Analisis Kesesuaian Standar Pelayanan Minimal (SPM) di Instalasi Gizi RSUD Syarifah Ambami Rato Ebu Bangkalan Madura - Shelviana Dalia Putri; Amalia Ruhana; Rahayu Dewi Soeyono; Noor Rohmah Mayasari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Minimum service standards are about the quality of basic services which are an obligatory matter for the region that every citizen has the right to obtain at a minimum. So each hospital can implement and fulfill services in accordance with the minimum service standards that have been set. Nutrition services in hospitals can be said to be of quality if they have met 3 indicators related to minimum standards of service in nutrition services, where these are accuracy of food distribution (≥ 90%), accuracy of diet (100%), food waste (≤ 20%) (Ministry of Health , 2008). This study aims to determine the timeliness of food distribution to patients, determine the accuracy of the type of diet to patients and food waste to patients in the Asoka ward of Syarifah Ambami Rato Ebu Regional Hospital. The type of research used is descriptive quantitative with a cross sectional research design. This research was conducted in November at Syarifah Ambami Rato Ebu Bangkalan Regional Hospital. The subjects in this study were 169 inpatients in the Asoka room for 10 days. The data collection technique was carried out using the observation method. Observations consist of data on the timeliness of food distribution, data on the accuracy of the diet and data on patient food waste. The data analysis technique used is univariate. The results of the research stated that the average results for the timeliness of food distribution were 74%, the accuracy of the type of diet was 100% and the food waste was 27%. Thus, it can be interpreted that the indicator of timeliness of distribution of food and food waste has not yet reached the SPM success indicator, while the accuracy of the type of diet has reached the SPM success indicator.